Contribution of Acute Renal Cortical Necrosis to Acute Kidney Injury: A 25-year experience from a tertiary care renal unit in Pakistan: Acute Kidney Injury and Acute Cortical Necrosis - Naqvi, Rubina; Jafry, Nazrul; Shaikh, Sana; Rashid, Rahma; Malik, Shaheera; Mubarak, Muhammad (Pakistan Journal of Kidney Diseases, 2025)
Background: Acute cortical necrosis (ACN) is a rare contributing factor to acute kidney injury (AKI). The present study aims to report clinico-pathological profile and outcome of ACN in the setting of AKI. Patients and Methods: This study was carried out at XXXXXXXXX. Subjects for the study comprised a cohort of 349 patients, (6.2% of total AKI) seen over a period of 25 years. AKI was defined according to KDIGO guidelines and diagnosis of ACN was based on radiological or histological findings. Results: From January 1990 to December 2014, 5,623 adult patients presented with AKI. Among these, 349 (6.2%) were found to have ACN. The mean age of ACN cohort was 29.33 ± 7.85 years. The major contributing cause was obstetrical AKI 286 (82%). On presentation 342 (98 %) were oligo-anuric. Histological diagnosis was available in 89 (25.50 %) cases, in 47 (53%) the pattern was diffuse and in 42 (47%) it was patchy. In rest, diagnosis was based on radiological findings. Hemodialysis was done in 346 (99.4 %). Complete recovery was seen in 9 (2.6 %), partial recovery in 76 (22%), chronic kidney disease (CKD) developed in 57 (16 %), end stage renal failure (ESRF) in 202 (58 %) while 5 (1.4 %) died during acute phase of illness. Conclusion: ACN is still encountered as a cause of AKI. Some patients may remain dialysis free even with diffuse pattern on histological examination and this population should be closely monitored to avoid nephrotoxic exposure.